Persisting metallic bullet inside the brain: The role of the speech language pathologist in the assessment and management of communication skills in traumatic brain injury based on a single case study - Priyanka EM Vas Naik; Thomas Zacharia; Jensy Gangan Kuniyil; Shwetha Sada (Wolters Kluwer Medknow Publications, 2016)
To acquire more knowledge on the communication skills after traumatic brain injury (TBI) caused due to gunshot with the bullet sustained in the brain. Formal speech, language, voice, hearing, and swallowing functions were evaluated using several tests and an informal assessment of reading, writing, and arithmetic skills were performed. Results of the evaluation gave a diagnosis as global aphasia with spastic dysarthria. Moderate to severe impairment was observed in the swallowing function. Right hemisphere functions were severely affected except for the music perception. On hearing screening, otoacoustic emissions were present in both the ears suggesting a normal outer hair cell function. The present study hence outlined the speech and language characteristics secondary to TBI with a persisting metallic bullet in the brain. Therefore, it is important that a speech language pathologist plays a role in the comprehensive assessment and management of individuals with TBI to provide a better quality of life.